EMPOWERING MOTHERS HOME APPLIANCES THROUGH STUDY CAREER MLM (MULTI LEVEL MARKETING) WITH CAPITAL SOCIAL - Ariani, Dian Meta; Rosita, Tita (IKIP Siliwangi Bandung, 2020)
One of the efforts undertaken by community members, especially housewives in meeting their needs, is to trade or run a business. The trading business they run requires a lot of networks consisting of upline and downline, so that the social relations that exist between upline and downline really require social capital. Tupperware is a product that uses the MLM marketing method with a worldwide trademark and has a reputation as an exclusive manufacturer of household appliances. The research method used is descriptive qualitative. The location of this research is the office of Tupperware PT. Fajar Puncak Pratama Bandung. With a sample of two manager, two team captain and three consultants. The research objective is to find out the form of social capital owned by business people in the Tupperware MLM community and the constraints faced. Data collection techniques used were observation and interviews. The results showed that 1) One of the Tupperware branches in Bandung was PT. Fajar Puncak Pratama, which is owned by Ms. Sofia Agnani. 2) Social Capital that is built into Tupperware members includes three things, namely, networking, norms, trust. 3) There are two obstacles faced in maintaining social capital for the continuation of the Tupperware MLM business, namely the denial of agreement and the emergence of unusual requirements.The conclusion of this research is Tupperware Business in Bandung, one of which is centered in the office of PT. Fajar Puncak Pratama has become an MLM business that can help improve community empowerment, especially housewives, as one of the targets in developing this business.